Prevalence of Functional Dentition in a Group of Mexican Adult Males - Minaya-Sánchez, Mirna; Medina-Solís, Carlo Eduardo; Casanova-Rosado, Juan Fernando; Vallejos-Sánchez, Ana Alicia; Casanova-Rosado, Alejandro José; Márquez-Corona, María de Lourdes; Mendoza-Rodríguez, Martha; Maupomé, Gerardo (Puerto Rico Health Sciences Journal, 2017)
Objective: To determine the prevalence of functional dentition and associated periodontal variables in a sample of Mexican adult males. Methods: A cross-sectional study of 161 policemen in Campeche, Mexico, was carried out. A clinical examination using an electronic probe was used to collect variables (dental plaque, periodontal pockets, gingival recession, suppuration, and bleeding on probing) on 6 periodontal sites (a maximum of 168 sites, excluding third molars). Sociodemographic, socioeconomic, and behavioral variables were collected through a self-administered survey. Functional dentition was defined as having 21 or more natural teeth. Data were analyzed with STATA 11.0, using logistic regression models. Results: Mean age was 38.3 (±10.9) years. The prevalence of having a functional dentition was 83.8% in the sample. The odds of having a functional dentition declined with age (odds ratio [OR] = 0.93), having diabetes (OR = 0.27) and with having a high percentage of sites with plaque (OR = 0.77), with bleeding on probing (OR = 0.97), and with gingival recession (OR = 0.82). Conclusion: While a large proportion of subjects had a functional dentition in this community-dwelling sample of adult Mexican males, the likelihood of their having a functional dentition decreased with age, with their having been diagnosed with diabetes, and with assorted negative indicators of periodontal/gingival status.